IMPLEMENTASI PEMBELAJARAN LITERASI DALAM MATA PELAJARAN GEOGRAFI DI SMA NEGERI 4 BUKITTINGGI TAHUN AJARAN 2020/2021 - mas nani; Khairani Khairani (JURUSAN GEOGRAFI FIS UNP, 2020)
This study aims to describe: (1) planning literacy learning in geography subjects, (2) implementing literacy learning in geography subjects, (3) literacy learning outcomes in geography subjects. This research uses a mixed approach (mixed methods) with a case study method. The subjects of this study were geography teachers and students of class XI IPS 1 of SMA Negeri 4 Bukittinggi. Data collection techniques using observation, questionnaires, interviews, and documentation. Data analysis techniques using the interactive model of Miles and Huberman consisting of data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that: (1) planning designed by the teacher by making a Learning Implementation Plan (RPP) in the implementation of literacy learning in geography subjects, (2) the implementation of literacy learning has been carried out in accordance with the Learning Implementation Plan (RPP), (3 ) literacy learning outcomes in the cognitive aspects show that 32 students who achieved KKM scores with an average of 83.00 percentage 91.43%. In the affective aspects of literacy learning successfully attract learners' interest in learning by reaching a high category (77.14%). In psychomotor aspects through the assignment to make a summary of the material with an average value (84.71). Keywords: Literacy, learning, geography